Underwater Acoustics - Bourennane, Salah (IntechOpen, 2012)
The field of acoustic engineering has many various potential applications, such as in ocean science research and homeland security. This book provides cutting-edge knowledge in current techniques and technologies, such as the adaptive technique for underwater communication, array processing and the CI/OFDM system. One chapter takes inspiration from the natural world in proposing a new bio-inspired ranging approach for resolution purposes. Technologies such as high-resolution array processing methods can also be used to locate underwater objects in sediment, as one chapter shows. Finally, two contributions cover the applications of narrowband interference suppression and iterative equalization, and decoding schemes. Given the scope of the book, it will be required reading for researchers and engineers in the field.